Exploring impact of future flexible working model evolution on urban environment, economy and planning - Rongrong Yu; Matthew Burke; Nowar Raad (Journal of Urban Management, 2019)
This paper aims to explore the impact of future flexible working model (FWM) evolution on urban environment, economy and planning. Working models are changing, evolving over several decades towards flexibility and mobility. Major cities are witnessing emerging alternative workplace models, such as coworking spaces, digital working hubs, on-demand spaces, and office clubs. These trends inevitably bring significant changes of flexible working hours, modified workplace business operations, different urban facilities requirements, and new workplace location options. However there remains a lack of understanding of the impact of such flexible modern workplaces on urban development. To address this issue, the current paper adopts a systematic literature review method, discusses the historical evolution and various types of FWM, and explores the impact of such FWMs on urban environment, economy and planning. This research leads to enhanced understanding, planning and management for the future challenges of next-generation working models in major cities, and brings potential direct benefits to urban development and the economy.
Keywords: 710; Flexible working model; Systematic literature review; Urban environment; Economy; Urban planning